Floral design GaN crystals: low-resistive and low-dislocation-density growth by oxide vapor phase epitaxy. (27th August 2021) - Takino, Junichi; Sumi, Tomoaki; Okayama, Yoshio; Kitamoto, Akira; Usami, Shigeyoshi; Imanishi, Masayuki; Yoshimura, Masashi; Mori, Yusuke
Abstract: GaN crystal growth mode in the oxide vapor phase epitaxy (OVPE) method, which simultaneously provides low electrical resistance and low threading dislocation density (TDD), has been investigated in detail. The results clarified that these qualities can be achieved by the expression of numerous inverted pyramidal pits, called three-dimensional (3D) growth mode. This mode reduced TDD from 3.8 × 10 6  cm −2 to 2.0 × 10 4  cm −2 for 1 mm thick growth because the threading dislocations (TDs) converged to the center of each pit. Moreover, when the crystal surface after polishing was observed by photoluminescence measurement, peculiar floral designs reflecting the distribution of oxygen concentration were observed over the entire surface. In addition, the etch pits exhibited TDs in the center of each floral design. On the basis of our results, we proposed that the 3D-OVPE-GaN will serve as a key material for improving the performance of vertical GaN devices.